The anarchivist-narrators of Milton Hatoum - Sousa, Rayniere Felipe Alvarenga de (2024)
This article aims to analyze the presence of the narrator-anarchivist in two novels by Milton Hatoum, Cinzas do Norte (2005) and A Noite da Espera (2017). The contribution to an episteme that amalgamates the concept through a bias that is not only conceptual, but also aesthetic, launches an alternative to deepen the anarchive process as a phenomenon enabled to promote readings with a critical content around political, social, historical materialities, as well as artistics, mainly literary. In order to achieve the purpose of the study, it is fundamental to resume concepts such as the archive, the traces and the figure of the collector, so that the practice of excavation between the lines of the analyzed novels can be strengthened. In this way, anarchiving operates as an aesthetic-conceptual instrument for the future, the new status of a fractured society. Therefore, literature influences a reflective task about human conditions, being necessary to anarchive in order not to succumb to the destruction of constructs in the present time.